15 years of PhosphoSitePlus®: integrating post-translationally modified sites, disease variants and isoforms. Issue Volume 47:Issue D1(2019) (16th November 2018) - Hornbeck, Peter V; Kornhauser, Jon M; Latham, Vaughan; Murray, Beth; Nandhikonda, Vidhisha; Nord, Alex; Skrzypek, Elżbieta; Wheeler, Travis; Zhang, Bin; Gnad, Florian
Abstract: For 15 years the mission of PhosphoSitePlus ® (PSP, https://www.phosphosite.org ) has been to provide comprehensive information and tools for the study of mammalian post-translational modifications (PTMs). The number of unique PTMs in PSP is now more than 450 000 from over 22 000 articles and thousands of MS datasets. The most important areas of growth in PSP are in disease and isoform informatics. Germline mutations associated with inherited diseases and somatic cancer mutations have been added to the database and can now be viewed along with PTMs and associated quantitative information on novel 'lollipop' plots. These plots enable researchers to interactively visualize the overlap between disease variants and PTMs, and to identify mutations that may alter phenotypes by rewiring signaling networks. We are expanding the sequence space to include over 30 000 human and mouse isoforms to enable researchers to explore the important but understudied biology of isoforms. This represents a necessary expansion of sequence space to accommodate the growing precision and depth of coverage enabled by ongoing advances in mass spectrometry. Isoforms are aligned using a new algorithm. Exploring the worlds of PTMs and disease mutations in the entire isoform space will hopefully lead to new biomarkers, therapeutic targets, and insights into isoform biology.